The Role of Antisiphon Devices in the Prevention of Central Ventricular Catheter Obliteration for Hydrocephalus: A 15-Years Institution's Experience Retrospective Analysis - Dimitrios Panagopoulos; Georgios Strantzalis; Maro Gavra; Efstathios Boviatsis; Stefanos Korfias (MDPI AG, 2022)
Shunt over-drainage in patients harboring a ventriculoperitoneal shunt constitutes one of the most devastating, and difficult to manage, side effects associated with this operation. Siphoning is one of the most important contributing factors that predispose to this complication. Based on the fact that the predisposing pathophysiologic mechanism is considerably multiplicated, amelioration of that adverse condition is considerably difficult to achieve. A lot of evidence suggests that the widespread utilization of gravitational valves or antisiphon devices is of utmost importance, in order to minimize or even avoid the occurrence of such complications. The recent literature data highlight that gravity-related, long-lasting shunt over-drainage consists of a momentous factor that could be considered one of the main culprits of central shunt failure. A lot of efforts have been performed, in order to design effective means that are aimed at annihilating siphoning. Our tenet was the investigation of the usefulness of the incorporation of an extra apparatus in the shunt system, capable of eliminating the impact of the siphoning effect, based on the experience that was gained by their long-term use in our institution. A retrospective analysis was performed, based on the data that were derived from our institution's database, centered on patients to which an ASD was incorporated into their initial shunt device between 2006 and 2021. A combination of clinical, surgical, radiological findings, along with the relevant demographic characteristics of the patients were collected and analyzed. We attempted to compare the rates of shunt dysfunction, attributed to occlusion of the ventricular catheter, in a group of patients, before and after the incorporation of an anti-siphon device to all of them. A total number of 120 patients who have already been shunted due to hydrocephalus of different etiologies, were managed with the insertion of an ASD. These devices were inserted at different anatomical locations, which were located peripherally to the initially inserted valvular mechanism. The data that were collected from a subpopulation of 17 of these patients were subjected to a separate statistical analysis because they underwent a disproportionately large number of operations (i.e., >10-lifetime shunt revisions). These patients were studied separately as their medical records were complicated. The analysis of our records revealed that the secondary implementation of an ASD resulted in a decrease of the 1-year and 5-year central catheter dysfunction rates in all of our patients when compared with the relevant obstruction rates at the same time points prior to ASD insertion. According to our data, and in concordance with a lot of current literature reports, an ASD may offer a significant reduction in the obstruction rates that is related to the ventricular catheter of the shunt. These data could only be considered preliminary and need to be confirmed with prospective studies. Nevertheless, this study could be considered capable of providing supportive evidence that chronic shunt over-drainage is a crucial factor in the pathophysiology of shunt malfunction. Apart from that, it could provide pilot data that could be reviewed in order to organize further clinical and laboratory studies, aiming toward the assessment of optimal shunt valve systems that, along with ASD, resist siphoning.